Implementation of Green Accounting and Environmentally Friendly Work Culture in Increasing the Competitiveness of Local MSMEs - Sari, Gema Ika (Riwayat: Educational Journal of History and Humanities, 2025)
Global changes towards sustainability encourage Micro, Small, and Medium Enterprises (MSMEs) to adopt environmentally friendly business practices. Green Accounting and environmentally friendly work culture emerged as a strategy that can increase the competitiveness of MSMEs by integrating environmental aspects in business operations. This study aims to analyze the application of Green Accounting and environmentally friendly work culture in local MSMEs, as well as identify their impact on business competitiveness. The study also explores the supporting factors and constraints in the implementation of sustainability practices. This study uses a descriptive qualitative approach with observation methods, semi-structured interviews, and documentation. Data was collected from a number of MSMEs in Grogol District, Cilegon, who have begun to adopt the concept of sustainability in their businesses. Thematic analysis is used to identify patterns and relationships between Green Accounting, environmentally friendly work culture, and business competitiveness. The study found that the implementation of Green Accounting is still in its infancy, with a focus on energy efficiency and waste reduction. An eco-friendly work culture is beginning to be implemented, although it is still limited to basic aspects such as plastic reduction and energy savings. The positive impact of this practice includes increased operational efficiency, better business image, and increased customer loyalty. However, challenges such as lack of understanding, technological limitations, and lack of supporting policies are still the main obstacles to implementation.